The Effect of Social Media Activities on Purchase Intention Study on Somethinc, A Local Skincare Brand in Indonesia - Auddie Indira Riyadi; Karto Adiwijaya (Universitas Negeri Malang, 2023)
The sales of the skincare industry in Indonesia increase from year to year. Along with the increase in social media use, it results in newcomers in the local brand sector; one is a brand called Somethinc. This study analyses social media activities (SMA) regarding purchase intention over a local skincare brand in Indonesia. This research was built using quantitative cross-sectional sampling with a total of 258 samples who lived in Jabodetabek. They are following Somethinc on social media, especially its Instagram @somethincofficial, yet they have never purchased Somethinc products. The data were analyzed using the SEM method through the SmartPLS 3.2.9 application. The results show that SMA has direct influences on brand equity, and brand equity influences purchase intention. Moreover, SMA also has a direct effect on purchase intention. This study proves that social media activities (SMA) significantly increase brand awareness, brand image, and purchase intention. The presence of customization, interactions, eWOM, and trendiness further enhance the positive effect. This means that managers must provide the latest and relevant information about their products in all cases. Keywords: Social media activities, Brand equity, Purchase intention, Instagram, Local brand, Skincare